An active noise barrier with unidirectional secondary sources - Chen, Weisong (2011)
An active noise barrier with unidirectional secondary sources is investigated in this paper, where the unidirectional secondary source consists of two closely located loudspeakers with pre-adjusted phase difference. The secondary sound field of the unidirectional sources is adjusted to maximally match the primary